Astrología y mitología en los manuscritos ilustrados de Alfonso X El Sabio - Domínguez Rodríguez, Ana (En la España Medieval, 2007)
A detailed and illustrated presentation of the astrological-mythological miniatures included in the original manuscripts of the works of Alfonso X of Castile, accompanied by the corresponding critical apparatus.